Different Perspectives Between Product and Marketing Division towards Product Critical Success Factors and Its Strategic Importance in Telecommunication Sectors - Utami, Rachmi Rida; Nasution, Reza Ashari (UI Scholars Hub, 2021)
Todays situations force telecomunication company to continuously evaluate, select and prioritize its product portfolio in order to determine the strategically important products. An analysis of critical success factors that determine product’s strategic importance acts as a good introduction to review and manage the product portfolio as well as to seek ways to develop the product. To achieve this, the company is required to have good alliances and collaborations between departments, develop a clear focus and seek innovative ways of doing business, particularly between marketing and product divisions. This study analyzed the alignment between product and marketing divisions of a telecommunication company in Indonesia, in determining the company’s strategic products. The results indicated that both divisions agreed on using financial performance and revenue as the most important criteria and sub-criteria for identifying strategic product. However, the divisions also faced some different visions in selecting alternative criteria. The Product divisions were more focused on technical spesification of product, while the Marketing division were more oriented on customer and market conditions. The study reported the consequences of these difference in practice.